Nursing Informatics Competency Assessment for the Nurse Leader: The Delphi Study. (April 2017) - Collins, Sarah; Yen, Po-Yin; Phillips, Andrew; Kennedy, Mary K.
Abstract : OBJECTIVE: The aim of this study was to identify nursing informatics competencies perceived as relevant and required by nurse leaders. BACKGROUND: To participate as a full partner in healthcare leadership among rapidly advancing health information technologies (HITs), nurse leaders must attain knowledge of informatics competencies related to their clinical leadership roles and responsibilities. Despite this increased need to engage in HIT-related decision making, a gap remains in validated informatics competencies specific to the needs of nurse leaders. METHODS: An environmental scan and 3-round survey using Delphi methods used with nurse leaders for competency identification were used. RESULTS: Between 26 and 41 participants responded to each Delphi round. Most nurse leaders acquired HIT knowledge through on-the-job training. We identified 74 competencies from an initial list of 108 competencies. CONCLUSION: This work can advance nursing practice to move beyond "on-the-job informatics training" to a more competency-based model of nursing informatics education and practice.